Some Techniques for Computing Wave Propagation in Optical Waveguides (Communications in Computational Physics, 2020)
Optical wave-guiding structures that are non-uniform in the propagation direction are fundamental building blocks of integrated optical circuits. Numerical simulation of lightwaves propagating in these structures is an essential tool to engineers designing photonic components. In this paper, we review recent developments in the most widely used simulation methods for frequency domain propagation problems.
Keywords: Optical waveguides; operator marching method; mode matching method; beam propagation method; bidirectional propagation methods; rational approximations.